Back Cover: Aggregation‐induced demulsification triggered by the hydrophilic fabric for the separation of highly emulsified oil droplets from water. Issue 1 (22nd February 2022) - Zhang, Yu‐Rong; Meng, Bi‐Wei; Hao, Bin; Ma, Peng‐Cheng
Abstract : Separation of highly emulsified oil in water is urgently needed in industry. In article number e131, Peng‐Cheng Ma and co‐workers develop a functional fabric with excellent performance to separate highly emulsified oil in water, aggregation‐induced demulsification process is proposed to reveal the mechanism behind such observation, and this is confirmed by studying the distribution of oil droplets in emulsion with a controlled separation degree.